Trick or Treat: Academic Buy-in to Third Stream Activities. (April 2016) - Watson, Derek; Hall, Lynne; Tazzyman, Sarah
This paper reports in part on a major study, carried out in 2013, in which data were collected from university senior executives and academics in the five university business schools in the North East of England: it focuses on the quantitative findings produced. Whilst prima facie evidence would suggest that universities are strategically embedding and integrating third stream strategies alongside first and second stream activities, a critical analysis of the research data revealed that this was clearly not the case. Empirical evidence from the research indicates that there are strategic failings in universities. This research contributes to the existing literature which highlights the academic pressures in embedding the third stream in higher education institutions.